New genus and new species of Cirripedia (Chthamalidae, Tetraclitidae, Archaeobalanidae and Balanidae) from the Middle Miocene of the faluns of Touraine (France) - Carriol, René-Pierre (Zootaxa, 2008)
This study of the faluns of Touraine provides further knowledge on the biodiversity and the distribution of the Middle Miocene Cirripedes. The occurrence of Tesseropora dumortieri (Fischer, 1866), previously known only from the Miocene of Rhône and Isère (France), of Actinobalanus collinsi Zullo & Perreault, 1989, previously known only from the Lower Miocene of Belgium, and Actinobalanus bisulcatus (Darwin, 1854a), never found in the Middle Miocene, is established and that of Actinobalanus dolosus (Darwin, 1854a) is refuted. A new genus of Archaeobalaninae (Paracti- nobalanus gen. nov.), three new Chthamalidae (Chthamalus grazianii sp. nov., Chthamalus nasus sp. nov., Chthamalus robustus sp. nov.), two new Archaeobalanidae (Paractinobalanus moronii sp. nov., Acasta vesiculosa sp. nov.) and a new Balanidae (Balanus nodulus sp. nov.) are described. The three new species of chthamalids represent the oldest known in the world.